Bridelia ferruginea Tea Consumption Improves Antioxidant Status in Individuals Living with Type 2 Diabetes - Collins Afriyie Appiah; Jennifer Ngounda; Mavis Boakye-Yiadom; Felix Charles Mills-Robertson; Mariette Nel; Rabia Johnson; Corinna Walsh (Diabetology)
Background: It is well-known that persistent hyperglycaemia predisposes individuals with diabetes to oxidative stress. Bridelia ferruginea Benth., a tropical African plant, is known for its antioxidant activity. Methods: This comparative cross-sectional study assessed the oxidative status and associated parameters in 70 individuals living with type 2 diabetes (ILWT2D) who were receiving standard diabetes treatment and consistently drank Bridelia tea (Bridelia group) compared to 92 ILWT2D receiving standard diabetes treatment only (comparator group). Lipid peroxidation assessed using thiobarbituric acid reactive substances (TBARS) served as an indicator of oxidative stress. In addition, the total antioxidant capacity (TAC), glycated haemoglobin (HbA1c), and dietary intake of antioxidant-rich foods were assessed. Results: The comparator group had significantly better glycaemic control [median HbA1c—7.7% (IQR 6.7–9.4)] than the Bridelia group [9.2% (7.6–11.4)], p = 0.001. The comparator group had been on metformin treatment for a significantly longer period than the Bridelia group (p < 0.0001). Participants in the comparator group consumed antioxidant-rich fruits more frequently (monthly basis) than those in the Bridelia group who ate fruits seldomly (p < 0.0001). There was no significant difference (p = 0.11) observed in oxidative stress levels between the Bridelia group and the comparator group [TBARS: 323.0 ng/L (287.5–374.0) and 317.0 ng/L (272.5–342.0), respectively]. Nonetheless, the Bridelia group had significantly higher antioxidant capacity (p = 0.001) compared to the comparator group [TAC: 1.01 mmol/L (0.93–1.10) versus 0.92 mmol/L (0.84–1.03), respectively]. Participants in the comparator group, who did not drink Bridelia tea, had been on longer metformin treatment with better glycaemic control. However, those who drank the Bridelia tea showed comparable levels of oxidative stress and exhibited elevated antioxidant levels compared to those who did not. Conclusions: Bridelia tea consumption may serve as a sustainable source of antioxidants; however, its effect on mitigating oxidative stress in ILWT2D requires further investigation, particularly given that no significant improvement in TBARS was observed. Future studies are needed to clarify the potential role of Bridelia tea in oxidative stress management in resource-limited settings like Ghana.